Experiences of Transnational Migrant Fathers in South Africa - Sekano, Onthatile (University of the Witwatersrand, Johannesburg, 2024)
In 1994, South Africa’s apartheid system came to an end, creating new opportunities for cross- border travel and the migration of foreigners from poor and rural areas seeking better economic opportunities. Due to South Africa being an economically stable African country, migration to South Africa has increased dramatically since 1994. However, there are challenges that migrants experience upon arriving in South Africa such as difficulties in acquiring legal documents, inadequate job prospects, appalling living circumstances, high crime rates, and the potential for xenophobia. This study aims to add to the body of knowledge of African migrants to South Africa specifically fathers who left their children behind, by using Bowen’s family system theory to explore their experiences as transnational migrants in South Africa. The sample for the study consisted of 10 Black African migrant men living in South Africa, and Braun and Clarke’s thematic analysis was used to analyse the collected data. The findings of this study show that African transnational migrants faced a variety of pull and push factors that prompted their migration to South Africa, as well as a variety of adjustment challenges such as xenophobia and difficulty finding work. The study also found that migration had an emotional and psychological impact on father-child relationships. Separation from their children had an impact on the migrants’ mental health, prompting them to develop a variety of coping strategies. The findings also indicate that not having their fathers present had a psychological impact on some children. Furthermore, the migrants used information and communication technologies (ICTs) to maintain regular contact with their children who had been left behind. The study discovered that, while participants used a variety of communication channels with their families, the majority preferred WhatsApp due to its ease of use and low cost. However, some participants lacked the financial resources to purchase smartphones for communication, while others were unable to cover the costs of staying in touch with their families. Furthermore, the study’s findings show that fathers’ ability to maintain relationships with their children is vii heavily influenced by the mothers of the children. Some mothers supported father-child relationships; others did not. In conclusion, the findings show that sending remittances allowed them to support their family members who were left behind. Furthermore, it was discovered that remittances were sent for a variety of reasons. For example, some fathers sent money to meet their families’ basic needs, while others sent money because they believed that providing for their families financially, fulfilled their role as fathers and breadwinners.
A research report submitted in fulfillment of the requirements for the Master of Arts in Social and Psychological Research, In the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Transnational migration; Information communication technologies; Family systems; African migrants; migrant fathers; SDG-5: Gender equality